Development of Mathematical Module Based on Guided Discovery to Develop Critical Thinking Ability and Learning Independence - Tianisa, Wan Tiara; Suparman, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
In mathematics learning the ability to think critically and the independence of learning is essential to be trained and developed. Therefore, it is necessary to design or compile materials or teaching materials that support the realization of critical thinking and student learning independence. The purpose of this study was to produce guided discovery-based mathematics modules to help develop critical thinking skills and learning independence of grade VII students of SMP/MTs. The research method used is a design research type formative evaluation. The research was conducted in two stages: the preliminary stage and the formative evaluation stage. The formative evaluation phase includes self-evaluation, prototyping (expert reviews and one-to-one, and small groups), as well as field tests. This study produced teaching materials in the form of mathematics modules on valid and practical social arithmetic materials. Then based on the process of development and analysis, the prototype of mathematics modules based on guided discovery has potential effects on critical thinking skills and learning independence.